Recurring Project Overrun and Project Management Problems in Engineering and Construction Industries - Lim, Cheong Seng (2001)
The purpose of this thesis is to present an account of the research conducted in the field of project management (PM). The broad problem area is the recurring project overrun problem. The three issues of concern are (1) the perceptions of a project, PM and their success, (2) the managerial implications of project execution problems, and (3) the verification of Baker's and Turner's theories of project success. The research made use of preliminary studies (unstructured interviews, case study, pilot study and structured interviews) to identify, refine and focus the issues for research. Survey research is used to derive the conclusive evidences in the Engineering and Construction (EC) industries in Malaysia. By the use of unstructured interviews, the research identified 28 factors believed to have caused project overrun problems. Among the 28 are four that have never been identified before by previous researchers. In a way, the research showed that unstructured interview is a useful methodology in identifying new ideas. The four new factors identified are the perceptions of individuals. The perceptions manifested in statements such as ''what constitute project success may vary", "inherited problems from earlier phases", "management does not care" and "projects are completed anyway". The influence and impacts of the ambiguities surrounding a project, PM and their success, on project performance could not have come to light but for the literature survey and unstructured interviews conducted. In the case study conducted, a list of 135 project execution problems of different type and complexity were identified. The managerial implications in terms of Henri Fayol's management function were studied. The pilot study and structured interviews helped in confirming the issues for investigation. The basic survey research then focused on the issues discovered in the exploratory studies for further investigation. Based on the preliminary studies theoretical frameworks and 10 hypotheses were formulated for testing.